Convergence of Business Cycles as A Confirmation of Oca Theory - Dizdarević Vesna; Volčjak Robert (Naše gospodarstvo/Our economy, 2012)
This paper examines business cycles in EU members and compares them with the business cycles of the economic and monetary union in Europe (EMU) members assumed to satisfy the optimal currency area (OCA). Accordingly, a multi-resolution decomposition of GDP growth signals is used, and correlation coefficients are com- puted for decomposed signals to assess the numerical values of synchronicities of business cycles. Our results reveal indications that areas adopting the euro in many ways confirm OCA theory and that the business cycles of most of the new EU members are not synchronized with the EMU; as such, these members might experience some difficulties if joining the euro too early.